Influence of heated, unheated whey protein isolate and its combination with modified starch on improvement of encapsulated pomegranate seed oil oxidative stability. (1st October 2020) - Comunian, Talita A.; Grassmann Roschel, Gabriela; da Silva Anthero, Ana Gabriela; de Castro, Inar Alves; Dupas Hubinger, Miriam
Highlights: Emulsions were stable under different salt concentrations and pH values. Reconstituted emulsions presented droplet size of 1.68–9.98 μm over 30 days. Sixteen fatty acids were identified in free and encapsulated pomegranate seed oil. WPI treatment was the best for protection of fatty acids present in the oil. Encapsulation of oil prevented the volatile compounds formation over time. Abstract: This study aimed at encapsulating pomegranate seed oil (PSO) by emulsification followed by spray drying using whey protein isolate (WPI) in its natural form, heated (Pickering), and combined with modified starch (WPI:Capsul®) as emulsifiers/wall materials. Emulsions were stable under different stress conditions. Pickering emulsions presented bigger droplet size (6.49–9.98 μm) when compared to WPI (1.88–4.62 μm) and WPI:Capsul® emulsions (1.68–5.62 μm). Sixteen fatty acids were identified in PSO. WPI treatment was considered the best formulation since it presented the highest fatty acid retention (68.51, 65.47, 47.27, 53.68, 52.95, and 52.28% for linoleic, oleic, punicic, α-eleostearic, catalpic, and β-eleostearic acids after 30 days-storage, respectively) and protected the oil against volatile compound formation (heptanal, (E, E)-2, 4-heptadienal, (Z)-2-heptenal, octanal, pentanal, (E)-2-hexenal, (E)-2-octenal, nonanal, (E)-2-decenal, and (E, E)-2, 4-octadienal), which did not occur with free PSO. Overall, encapsulation protected PSO against oxidation over time, which may allow the development of new functional foods.